Treatment discrimination among assistant coaches of women's teams - Cunningham, G. B.; Sagas, M. (Research Quarterly for Exercise and Sport, 2003)
The purpose of this study was to examine organizational treatment discrimination (i.e., when members of a group receive fewer rewards, opportunities, or resources than they legitimately deserve based on job-related criteria) in the context of women`s athletics. Data were collected from 170 assistant coaches of women`s teams (i.e., women`s basketball, softball, track, volleyball, soccer, and tennis). Results indicate that women`s perceived work experiences and outcomes were comparable, and sometimes better, than those of men. We present competing explanations for this finding. First, it is possible that these women were not subjected to treatment discrimination. Alternatively, it is possible that this demonstrates the existence of the"paradox of the contented working woman." Additional analyses indicate that work experiences explained a large portion of the variance in organizational commitment and turnover intentions, thereby demonstrating their importance in the workplace.